KONTRADIKSI ANTAR DALIL DAN CARA PENYELESAIANNYA PRESPEKTIF USHULIYYIN - Ahmad Atabik (Program Studi Hukum Keluarga Islam, 2015)
ABSTRAKThis article describes method in the study of ushul fiqh on contradictory dalil and the ways ushuliyyin solved this problem. In fact, there is no contradiction in the law, rather, sometimes mujtahid disputed over two arguments. Mujtahid of the classic era has been working in many ways to find solution of the problems. They are jam’u wa at-taufiq (comprise and compromise), tarjih (favor) and nasakh (abrogating). If al-jam’u is not possible to compromise among dalil, then mujtahid used tarjih (favoring one of them). However, should tarjih is impossible, then the last method is naskh, ie the first coming text is cancelled by the later one in chronological order. If they did not know which text came first, then tawaqquf was applied.